Adapting HR Practices for Remote Work: Lessons from the Post-Pandemic Era, Case Study at Uniska MAB Banjarmasin - Ambarwati, Riris; Nadeak, Bernadetha; Sofyan, Hady; Rosid, Abdul; Priatna, Isep Amas (PT Inovasi Pratama Internasional, 2024)
In a global context influenced by the pandemic, HR adaptations to support remote work are important for organizational continuity and productivity. This research highlights the lessons learned from a case study at Uniska MAB Banjarmasin, which effectively adapted their HR practices in the post-pandemic era. Diverse research methods, including case studies, in-depth interviews, document analysis, and participant observation, provide in-depth insight into the adaptation process. The research results show that Uniska MAB Banjarmasin experienced significant changes in work patterns, performance evaluation, and reward policies as a response to remote work. Despite emerging challenges, such as remote management and work-life balance, the adaptation of effective strategies, such as technology training and an open communication approach, has resulted in increased employee engagement, productivity and job satisfaction. The implications of this research are not only practical, with recommendations for other organizations wishing to adopt similar practices, but also theoretical, providing a deeper understanding of HR management in the context of remote work. By considering the challenges overcome and lessons learned from Uniska MAB Banjarmasin, this research highlights the potential for positive adaptation of HR practices to support organizational success in facing rapidly changing work environments.